Radiolabelling of Antibodies: Methods and Limitations - Andres, R. Y.; Schubiger, P. A. (Nuklearmedizin - NuclearMedicine, 1986)
The development of a labelled antibody for radioimmunoscintigraphic tumor localisation necessitates a major optimisation procedure to carefully balance factors such as radionuclide, anchoring site on the antibody, method of labelling and addition of radioprotective agents. Even under ideal conditions radiolytic and enzymatic degradation of the biologically active antibody cannot be avoided. The resulting radioactive fragments will exhibit organ distribution patterns different from those of the parent antibody and may pose a major obstacle to scintigraphy of certain organs such as liver, kidney and spleen.